Czas w uczeniu się. Analiza krytyczna perspektywy obiektywistycznej - Maria Groenwald (Problemy Wczesnej Edukacji)
The paper is a critical analysis of time in learning, functioning in the objectivist approach to education. Referring to results of anthropological research and literary studies in this field, I justify in it the thesis that in transmissive teaching becomes an instrument for subjugating children. It is supported by the following realities of schooling: imposed time of children’s stay at school, an obligation to do homework and timeframe of “covering” textbooks, which leads to pupils being overloaded with school learning, wasting time at lessons, repeating years, or even being halted in time. The effect of the time of learning being seized by the time of teaching is petrification of the bureaucratic management of time, pretended learning and tabooism of the disturbing phenomenon of the temporary regime of learning.